Aportes de la práctica pedagógica investigativa de profundización a la formación de los futuros licenciados - Guzmán-Sierra, Andrés Julián; Hernández Espitia, Nairo Yezid (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This review article has as main objective to disseminate the results of the information consolidated in the different processes of Pedagogic Practice suitable Investigative Deepening in the second half of the year 2017 of the LEB. You can see statisti- cal data that make mention of the academic development and training program that showed students the tenth semester. The methodology of action was merely descriptive-interpretative development from a mixed approach, where supported by the techniques of gathering information and critical analysis-reflective of the collected documents, allowed the analysis of the results obtained in a systematic and coherent. As a conclusion, it was attributed to the importance of collecting and organizing this information periodically in order to establish the general database of the academic program.